Implementasi Sistem Manajemen Bandwidth Berbasis Mikrotik Menggunakan Metode NDLC (Network Development Life Cycle) dengan Pemanfaatan Jaringan Komputer Pada Kos Kaca Depok - Wanda Faiz Ibrahim; Cendra Harmon (Teknik Informatika Universitas Pamulang, 2026)
This study examines the implementation of a MikroTik-based bandwidth management system using the Network Development Life Cycle (NDLC) approach in a computer network environment at Kos Kaca Depok. The primary challenges identified include unequal bandwidth distribution and frequent network congestion resulting from the increasing internet demands of boarding house residents. To address these issues, the NDLC framework—comprising analysis, design, implementation, and evaluation stages—was employed to develop and deploy the bandwidth management system in a structured and systematic manner. Bandwidth allocation was regulated using MikroTik features such as Simple Queue and Queue Tree to ensure fair and measurable distribution among users. Network performance was evaluated by analyzing Quality of Service (QoS) parameters, including throughput, latency, and jitter, before and after system implementation. The results demonstrate a significant improvement in network performance, characterized by increased throughput as well as reduced latency and jitter. Furthermore, user feedback indicates enhanced satisfaction with respect to network stability and access speed. These findings confirm that the proposed MikroTik-based bandwidth management system, developed through the NDLC approach, is effective in improving network performance and supporting digital activities in shared residential environments.